2023
DOI: 10.1002/cl2.1330
|View full text |Cite
|
Sign up to set email alerts
|

Montessori education's impact on academic and nonacademic outcomes: A systematic review

Abstract: BackgroundMontessori education is the oldest and most widely implemented alternative education in the world, yet its effectiveness has not been clearly established.ObjectivesThe primary objective of this review was to examine the effectiveness of Montessori education in improving academic and nonacademic outcomes compared to traditional education. The secondary objectives were to determine the degree to which grade level, Montessori setting (public Montessori vs. private Montessori), random assignment, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 142 publications
0
0
0
Order By: Relevance
“…While outcomes from schools that adhere well to the AMI program (including AMI-trained teachers, specific 3-year age groupings, long work periods, full sets of materials, and relatively large classes with high child:teacher ratios) are strong (Lillard and Else-Quest, 2006;Lillard, 2017;Denervaud et al, 2019Denervaud et al, , 2020aGuerrero et al, 2023), other implementations are in need of more rigorous study. Even despite the range of variation in how Montessori is implemented, two new and separate meta-analyses of Montessori, one originating in the United States and the other in France, both reported positive effects on both academic and nonacademic outcomes (Demangeon et al, 2023;Randolph et al, 2023). In the next section the structure of Montessori education is described, followed by an explanation of how the pedagogy is constructivist, child-centered, and compatible with culturally responsive pedagogy.…”
Section: Montessorimentioning
confidence: 99%
See 1 more Smart Citation
“…While outcomes from schools that adhere well to the AMI program (including AMI-trained teachers, specific 3-year age groupings, long work periods, full sets of materials, and relatively large classes with high child:teacher ratios) are strong (Lillard and Else-Quest, 2006;Lillard, 2017;Denervaud et al, 2019Denervaud et al, , 2020aGuerrero et al, 2023), other implementations are in need of more rigorous study. Even despite the range of variation in how Montessori is implemented, two new and separate meta-analyses of Montessori, one originating in the United States and the other in France, both reported positive effects on both academic and nonacademic outcomes (Demangeon et al, 2023;Randolph et al, 2023). In the next section the structure of Montessori education is described, followed by an explanation of how the pedagogy is constructivist, child-centered, and compatible with culturally responsive pedagogy.…”
Section: Montessorimentioning
confidence: 99%
“…Third, studies also suggest that at least in properlyimplemented Montessori, children including those from groups typically disadvantaged in this country such as low-income children (Lillard et al, 2017) and children of color (Lillard et al, 2023b), achieve as good or better academic and social outcomes than children at other (typically TTC) schools (Denervaud et al, 2019(Denervaud et al, , 2020bLillard, 2019;Snyder et al, 2022). One of the meta-analyses just cited used only studies with evidence of baseline equivalence; it showed that compared to traditional education, Montessori has significant positive impacts on both academic (reading, math, and so on) and non-academic (executive function, creativity, and so on) skills (Randolph et al, 2023). Proficiency levels on test scores are generally higher, and racial and economic achievement gaps on those tests are smaller (Snyder et al, 2022).…”
Section: How Cei Models Address the Ttc Problemsmentioning
confidence: 99%
“…This may especially be so later in development, when the desired and expected learning progress is more quantifiable for a child herself, given the development of children's metacognitive abilities (de Eccher et al, 2023). Furthermore, such peer learning has been shown to be highly effective for older children in school settings (Randolph et al, 2023;Topping, 2005).…”
Section: Looks To Facementioning
confidence: 99%
“…Children's tendency to attribute knowledge, status, and competence to adults might facilitate their learning because focusing on what adults are attending to and talking about might be more informative than focusing on a child or a baby, who may know only slightly more than the infant themselves. Other social theories also emphasise the valuable impact of slightly older peers (Vygotsky, 1962) and the role of peers in early development is the basis for the principles underlying Montessori classrooms (Montessori, 1949) with children of larger age ranges allowing for learning from slightly older and more knowledgeable peers (Randolph et al, 2023). Zmyj and Seehagen (2013) write in their review that, while children consider adults as knowledgeable social partners, peers may be interesting for other reasons given the higher similarity between the peer's and a child's own (motor) skills and interests.…”
Section: Introductionmentioning
confidence: 99%